Engine performance and exhaust emission of diesel dual fuel engine fuelled by biodiesel, diesel and natural gas - Abdul Majid, Z. (Penerbit UTM Press, 2016)
The performance and exhaust emission of 6 cylinder four stroke direct injection diesel dual fuel (DDF) engine were investigated, the duel fuel used is corn oil methyl esters consist of 5%, 10%, 15% and 20% blends with diesel and compressed natural gas (CNG). Experiment was conducted at a fixed compression ratio of 17.5:1 with variance of engine speed 1400, 1800, 2400 and 2600 rpm. Combination of Biodiesel and CNG showed a better result on engine performance in terms of horse power and engine torque compared to other types of tested fuel. The substantial decrease of 25.6 % in exhaust emission flue was observed, giving lower value of UHC and nitrogen oxide (NOx). However, when the fuel is blended with CNG, a poor performance on exhaust emission was recorded, which include carbon dioxide (CO2), carbon monoxide (CO), unburned hydrocarbon (UHC) and nitrogen oxide (NOx) due to presence of CNG in fuel.